2011
DOI: 10.1002/anie.201102113
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Molecule Analysis Using DNA Origami

Abstract: During the last two decades, scientists have developed various methods that allow the detection and manipulation of single molecules, which have also been called "in singulo" approaches. Fundamental understanding of biochemical reactions, folding of biomolecules, and the screening of drugs were achieved by using these methods. Single-molecule analysis was also performed in the field of DNA nanotechnology, mainly by using atomic force microscopy. However, until recently, the approaches used commonly in nanotech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
141
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(142 citation statements)
references
References 116 publications
0
141
0
1
Order By: Relevance
“…While an individual origami can serve as a template for up to 200 small devices, typically only a single multi-component electronic or optical device is constructed 10,12 . For many technological applications it would be desirable to organize origami into periodic arrays, for example, to allow wiring of electronic devices together, to create cooperative optical effects as seen in optical metasurfaces 17 , to create DNA 'etch masks' 18,19 or to enable easier extraction of single-molecule biophysical data 9,20 .…”
mentioning
confidence: 99%
“…While an individual origami can serve as a template for up to 200 small devices, typically only a single multi-component electronic or optical device is constructed 10,12 . For many technological applications it would be desirable to organize origami into periodic arrays, for example, to allow wiring of electronic devices together, to create cooperative optical effects as seen in optical metasurfaces 17 , to create DNA 'etch masks' 18,19 or to enable easier extraction of single-molecule biophysical data 9,20 .…”
mentioning
confidence: 99%
“…The notion of using DNA as a building block dates back to the 1980s, when N. C. Seeman started working on DNA-based materials. 214 On one side, his seminal work spurred the fast development of what is today known as DNA nanotechnology, 215 which employs DNA as a tool to build molecular motors, 216 logic gates 217 and finite-sized objects with pre-designed shapes such as polyhedra, 218,219 tubes 220,221 or even complicated, irregular structures, e.g., DNA origami, 222 which can be used as nano-scaffolds for high precision experiments [223][224][225] or even as drug delivery vectors. 213 On the materials science side, the early results obtained by Seeman and others showed that DNA can also be used as a building block for the generation of ordered and disordered bulk phases.…”
Section: Dna-based Systemsmentioning
confidence: 99%
“…Such structures have been typically assembled by folding a long 'scaffold' strand of viral single-stranded DNA (ssDNA) using multiple short ssDNA 'staple' strands; however, they can also be assembled without the use of a scaffold [5][6][7] . The strength of this technique has been demonstrated in a number of applications including control and study of molecular transport in cells [8][9][10] , drug delivery systems 11 , as platforms for single-molecule chemical reactions 12,13 , rulers for super-resolution microscopy 14,15 as well as nanopore biosensors [16][17][18] . Furthermore, the double helical structure of DNA offers the possibility of unique binding sites with a regular spacing of B7 nm (21 bp) along the helix and B3 nm perpendicular to the helical axis 19 which makes DNA origami perfectly suited as a platform for the assembly of multicomponent nanostructures 20,21 .…”
mentioning
confidence: 99%